Learning Media Development using Transformative Learning Strategy Android Application as a Distance Learning Support on Static Fluid - Sunaryo Sunaryo; Hadi Nasbey; Hilda Amelia (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
This research aims to develop and produce an Android application using a Transformative Learning Strategy as a Distance Learning on static fluid material. The research used Research and Development (R&D) method, which refers to the Dick and Carey model. The instrument was a questionnaire using a Likert scale and analyzed with a continuous line. According to media experts, this Android application had a validation test phase with a successful percentage of 96% according to matter experts and 80%. According to learners, this application trial was conducted to 30 students of class XI MIPA and physics educators/teachers at SMA Negeri 109 Jakarta with a percentage achievement of 77% according to educators and 83.21%. Based on these results, the data showed that the Android application using Transformative Learning Strategy as a Distance Learning on static fluid material is suitable media for learning physics.